Development of a Project-Based e-Module to Strengthen the Profile of Pancasila Students on Green Chemistry Materials in Senior High School - Hikmah, Nurul; Asyhar, Rayandra; Zurweni, Zurweni (Journal of Educational Learning and Innovation (ELIa), 2025)
The use of e-Modules currently plays a significant role in facilitating the learning process in classrooms, as modern technology enables effective and independent learning. This is particularly relevant in chemistry education, specifically in the topic of green chemistry, which extensively discusses environmental issues. The principles of green chemistry can be implemented in daily life by incorporating the strengthening of the Pancasila Student Profile. This study aims to explore the development process of an e-Module, its theoretical feasibility as assessed by subject matter experts and media experts, as well as teacher evaluations and student responses to the developed e-Module. The research adopts the Lee & Owens development model, which is adapted from ADDIE, utilizing interviews and questionnaires as research instruments. The e-Module product was validated by subject matter experts and media experts and evaluated by chemistry teachers. Trials were conducted on an individual and small-group basis. Data were analyzed qualitatively and quantitatively by calculating the average response scores and percentage of feedback. The validation results indicate that the e-Module received a score of 3.7 from subject matter experts (categorized as feasible) and 4.6 from media experts (categorized as highly feasible). Teacher evaluations yielded a score of 4.8 (highly feasible), while the individual trial reached 92.6%, and the small-group trial obtained 87.6%. Based on these results, it can be concluded that the developed e-Module is feasible for use in chemistry learning, with the reinforcement of the Pancasila Student Profile in the topic of green chemistry in senior high schools.